Efeitos do uso de probióticos sobre a qualidade de vida e atividade física em universitárias constipadas : estudo duplo-cego e randomizado - Kommers, Michelle Jalousie (2018)
Introduction: Constipation is characterized by unsatisfactory defecation, infrequency, symptom of incomplete evacuation or difficulty in stool passage. It often occurs in women impacting quality of life. The objective of this study was to analyze the effect of probiotic therapy containing 2 genders and 5 bacteria species versus placebo on quality of life in university women with intestinal constipation. Methods: Two-arm, double-blind, randomized controlled clinical trial with probiotic experimental group (n = 32) and placebo control group (n = 31). University women aged 20 to 40 years who self-reported suffering from intestinal constipation were selected using the criteria of Rome III. The sociodemographic, Patient Assessment of Constipation-Quality of Life (PAC-QOL) and International Physical Activity Questionnaire (IPAQ) and anthropometric measures were applied. The intervention occurred during 30 days in the pilot phase and 15 days in the main study phase. Statistical analysis was performed using the Mann-Whitney Shapiro-Wilk test and paired student's t-test, and the estimation of the relative risk (RR) treatment effect, absolute risk reduction (RAR), relative reduction of risk (RRR), number needed to treat NNT and odds ratio (OR). Results: The experimental group had improved quality of life in 23% (RAR = 23% and p <0.01) and the satisfaction was 87% (RAR = 87% and p <0.01) according to the PAC-QOL. For treatment, it was necessary to treat NNT = 4.35 constipated women in order to avoid the quality of life of 1 of these women. Also, for each NNT = 1.14 treated women, one was satisfied. The control group presented increased physical discomfort and psychosocial discomfort when they practiced vigorous physical activity. Conclusions: The use of supplements with a variety of probiotic bacteria has been shown to be effective and reduced physical discomfort and health concerns. However, university students who practiced vigorous physical activity and did not supplement with probiotics, physical discomfort and psychosocial discomfort increased. In summary, probiotic supplementation had a positive impact on the quality of life of constipated university women. Thus, if you change your lifestyle, you may benefit even more from bowel function. Registry trial: UTN: U1111-1196-9502 Url of the registry (trial url): http://www.ensaiosclinicos.gov.br/rg/RBR-5hnk3r/ Registration Number (trials Number: RBR-5hnk3r. Date of approval: 08/24/2017.